(untitled) (Research, Society and Development, 2024)
In recent years, several researchers have turned their attention to unraveling the relationships between money, happiness and mental health. Mental health is part of what sustains people’s individual and collective abilities to make decisions, establish relationships and shape the world. The aim of this study was to address questions about money, happiness and mental health. The methodology applied was an observational and cross-sectional study with a quantitative approach. For the results obtained, it was questioned how relationships with parents and interpersonal relationships can affect the mental and spiritual development of the participants. It can be seen that taboos such as alcohol and smoking affect individuals less than betrayal or distrust within relationships. Factors such as happy marriages, volunteer work, religion and financial control contribute to the individual’s better emotional and mental state. It is concluded that mental, emotional and financial success arises from mentally healthy people.